Formation of Udmurt rap - Victor L. Shibanov (Этническая культура)
Udmurt rap was an attempt to expand the horizons of the national literary and musical culture of the early 21st century, which was dominated by ethnofuturism at that time. The object of analysis is the Udmurt-language rap texts of P. Shibanov, B. Anfinogenov and A. Pikulev, who released their albums in the period 2008–2018. The purpose of the study is to identify the national characteristics of Udmurt rap texts. The leading research method is descriptive-analytical, using comparative techniques. The results of the analysis are as follows. P. Shibanov depicts the life of Udmurt students in a dormitory; adaptation to the modern city is presented in different aspects. B. Anfinogenov writes his texts in the style of an ethno-soundtrack, mixing Udmurt, Russian and English. His hero is self-sufficient in that he is an Udmurt and can represent his nation in the global world. A. Pikulev is paving the way from the rap subculture to the artistic and literary beginning; images of nature occupy an important place. Udmurt rap is not an expression of protest sentiments; it is aimed at improving the status of the native language.